2010
DOI: 10.1507/endocrj.k09e-349
|View full text |Cite
|
Sign up to set email alerts
|

Short-term intermittent PTH 1-34 administration enhances bone formation in SCID/Beige mice

Abstract: Parathyroid hormone (Pth) is an 84 amino acid polypeptide secreted by parathyroid glands in response to low serum calcium. The exogenous administration of PTH can induce both anabolic and catabolic actions in bone; however, such consequences depend upon how PTH is administered. Continuous PTH infusion, similar to the condition of hyperparathyroidism, initiates bone catabolism by enhancing resorption and decreasing formation. In contrast, when administered intermittently (by daily injection), PTH promotes bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The authors concluded from their work that intermittent PTH(1-34) for 3 weeks is sufficient to enhance bone formation without enhancing resorption. 41 In accordance with these considerations, our results indicate a significant anabolic effect of PTH , as evidenced by the enhanced expression of markers of osteoblastic differentiation and biomineralization and also by serum osteocalcin levels in the PTH(1-34)-treated mice.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The authors concluded from their work that intermittent PTH(1-34) for 3 weeks is sufficient to enhance bone formation without enhancing resorption. 41 In accordance with these considerations, our results indicate a significant anabolic effect of PTH , as evidenced by the enhanced expression of markers of osteoblastic differentiation and biomineralization and also by serum osteocalcin levels in the PTH(1-34)-treated mice.…”
supporting
confidence: 89%
“…Among others, osteocalcin was demonstrated to be influenced by PTH treatment under different conditions and in different mouse gene types. 41 The mentioned study demonstrated that serum osteocalcin levels were significantly increased after PTH exposure. The authors concluded from their work that intermittent PTH(1-34) for 3 weeks is sufficient to enhance bone formation without enhancing resorption.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Sections were then incubated at 37˚C for 15-20 min in freshly prepared acetate-tartaric acid buffer (pH 5.0) containing 0.5 mg/ml naphthol ASMX phosphate and 1.1 mg/ml Fast Red TR (TRAP substrate). After washing with distilled water, tissues were counterstained with aqueous haematoxylin and mounted with Vectamount (Vector Laboratories, Inc., Burlingame, CA, USA) (23).…”
Section: Methodsmentioning
confidence: 99%
“…The number of cells was determined in five tissue sections spanning 100 μm of tissue. Data are expressed as the mean number of cells per 1.0 mm of perimeter trabecular bone (23).…”
Section: Quantification Of Trap-positive Cellsmentioning
confidence: 99%